INTEGRATION OF DA'WAH AND LOCAL CULTURE:: An Analysis Of The Ritual Of Wiwit Mbako In Temanggung - Puspitasari, Isma; Ultriasratri , Alfri (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2023)
This paper explores the integration of Islamic da'wah with local culture through the Wiwit Mbako ritual, a traditional agricultural ceremony practiced in Temanggung, Central Java. The central research question investigates how Islamic values are communicated and embodied within this cultural tradition, particularly in the context of rural agrarian communities. Employing a qualitative approach, the study analyzes the Wiwit Mbako ritual as both a cultural and religious practice, focusing on key elements such as prayers (doa), communal meals (selamatan), and social gatherings (gotong royong). Through these ritualistic components, the paper examines how Islamic teachings—such as gratitude, trust in Allah, and communal solidarity—are contextualized and disseminated within a familiar, culturally resonant framework. The findings highlight the dual role of the Wiwit Mbako ceremony, which not only serves as an expression of thanksgiving for a successful tobacco harvest but also as a medium for Islamic da'wah, promoting social harmony and religious devotion. The paper concludes that the Wiwit Mbako ritual not only reaffirms the community's dependence on divine will but also strengthens the role of da'wah by blending Islamic messages with local customs, thereby enhancing their relevance and impact within an agrarian society. This fusion of religion and culture underscores the adaptability of Islamic da'wah in rural Indonesia, making it a vital tool for preserving both cultural identity and religious values.